Pengaruh Alkalinitas terhadap kelangsungan Hidup dan Pertumbuhan Ikan Lalawak (Barbodes sp.) - Yulfiperius Yulfiperius; Mozes R. Toelihere; Ridwan Affandi; Djadja Subardja Sjafei (Majalah Ilmiah Biologi BIOSFERA: A Scientific Journal, 2006)
This experiment was conducted to determine the effect of alkalinity on the survival rate and daily growth rate of Barbodes sp. The fish were reared in 12 aquariums with four different levels of alkalinity, i.e. 48, 78, 108 and 138 ppm. Each aquarium was filled with 10 fish of 12.25 to 12.64 gram in average body weight. The treatments were applied for 75 days. During the experiment, the fish were given commercial diet (pellet) of 5% rate of biomass weight at the frequency of three times a day. The results showed that the survival rate for all treatments was 100%, and the alkalinity suited for daily growth rate of fish lalawak was 78 ppm of CaCO3.